Antibacterial Activity Test of White Honey from Sumbawa NTB Againts Staphylococcus epidermidis - Vaidika, I Komang Satya; Wardoyos, Eustachius Hagni; Rahim, Adelia Riezka (Jurnal Biologi Tropis, 2024)
Staphylococcus epidermidis is the most common bacteria found on human skin that causes acne and is a coagulase-negative Staphylococcus species (CoNS). Resistance to methicillin is widespread, especially in Staphylococcus epidermidis bacteria or often called MRSE and is widespread globally ranging from 75-90%. Regarding antibiotic resistance, it is important to do research to find new alternatives to this problem. One of the natural antibiotics that can be used is honey which has benefits as an antibacterial because it has three systems that play a role in inhibiting bacterial growth, namely osmotic pressure, acidity and inhibine. The purpose of this study was to analyze the antibacterial effect of Sumbawa white honey on Staphylococcus epidermidis bacteria. The method used in this study was an analytical laboratory experiment with a Randomized Controlled Trial (RCT) type of post test only design. The method of making honey using disc diffusion was carried out 5 times at concentrations of 25%, 75%, 100%, positive chloramphenicol control and negative DMSO control. The results of the antibacterial test can be seen from the formation of the diameter of the inhibition zone on the disc paper. The results of the study obtained that at a concentration of 25% no inhibition zone could be formed, while in the 75% study an inhibition zone of 2.32 mm was formed and 100% of 6.71%. Based on the results of the antibacterial activity test, it can be concluded that the study on Sumbawa white honey at concentrations of 75% and 100% is included in the resistant/weak category and the activity is not effective in inhibiting the growth of S. epidermidis.